Evaluating the implementation of the New Medicine Service in England - Wells, Katharine M. (2014)
Community pharmacies in England provide a variety of services including essential services such as the dispensing of medicines, advanced services such as Medicine Use Reviews, and enhanced and locally commissioned services, for example the minor ailments scheme. In October 2011 a new advanced service called the New Medicine Service (NMS) was introduced. It aimed to improve adherence to newly prescribed medicines for patients with certain long term conditions and reduce medicines wastage. This thesis aims to evaluate the implementation of the NMS by exploring how the service was developed and implemented, identifying both potential and actual barriers and facilitators to NMS implementation, investigating the proportion of prescription items that are eligible for the service, and examining the uptake and provision of the service. In order to achieve this several studies were carried out. Interviews were conducted with stakeholders involved in the service’s development and implementation. Focus groups were conducted with community pharmacists complimented by interviews with superintendent pharmacists both before and after the introduction of the NMS. Data regarding the number of prescription items eligible for the service were collected in community pharmacies, and an analysis of service records for a large national chain of pharmacies was carried out. The studies determined that there were four stages to the development and implementation of the NMS; pre-negotiation, negotiations, the launch phase, and post-implementation. Both community pharmacists and superintendent pharmacists were enthusiastic about the potential of the service prior to the introduction of the service and anticipated good uptake of the service which was confirmed by post-implementation results. Several barriers were identified prior to implementation, the most important of which was the payment structure. Post-implementation results confirmed that the payment structure had affected NMS implementation, and direct observations in pharmacies, that the opportunity rate to provide the service was nearly half of the payment structure’s theoretical rate. Analysis of service data showed the uptake of the NMS was greater than the uptake of MURs in 2005. The findings of this thesis provide policy makers, pharmacy stakeholders, community pharmacists, and researchers with knowledge of how pharmacy services are developed. It also provides insights about factors that can facilitate or hinder service provision, including pharmacist attitudes towards a service, certain service and pharmacy characteristics (such as the ability to carry out telephone consultations), company encouragement to provide the service, the experience of conducting other pharmacy services, pharmacist workload, the accreditation procedure, and the services payment structure. These insights can be used to improve future pharmacy services’ implementation.